Environmental Factors Shape Water Microbial Community Structure and Function in Shrimp Cultural Enclosure Ecosystems - Hou, Dongwei; Huang, Zhijian; Zeng, Shenzheng; Liu, Jian; Wei, Dongdong; Deng, Xisha; Weng, Shaoping; He, Zhili; He, Jianguo (Frontiers in Microbiology, 2017)
The effect of environmental factors on water microbial communities has been extensively studied, but little is known in shrimp cultural enclosure ecosystems. We analyzed 16S rRNA gene amplicons to explore the principal environmental factors shaping the structure and function of microbial communities in shrimp cultural enclosure ecosystems from Guangdong and Hainan provinces, China. All high quality sequences were clustered into operational taxonomic units (OTUs) at the 97% similarity level, generating 659 to 1,835 OTUs per sample. The ten most abundant phyla were Proteobacteria, Bacteroidetes, Cyanobacteria, Planctomycetes, Actinobacteria, Verrucomicrobia, Firmicutes, Chlorobi, Chloroflexi and Chlamydiae. Canonical correspondence analysis (CCA) identified that salinity，total phosphate (TP), total nitrogen (TN), temperature and pH were the most important factors shaping the microbial community structure. The differences in microbial community structure between high and low salinity samples were explained by the changes in the relative abundances of some OTUs (e.g., OTU5, OTU19, OTU21, OTU39, OTU71). Meanwhile, the contribution of spatial distribution for microbial community assembly was investigated by aggregated boosted tree (ABT) analysis, showing that the spatial isolation was not the major factor to affect phylogenetic diversity and phylotypes of water microbial communities. Furthermore, we predicted water microbial community functional profiling with PICRUSt. Principal component analysis (PCA) suggested that salinity was a major contributor to the structure and function of microbial community. Collectively, these results showed that environmental factors influenced the structure and function of water microbial communities, while salinity was the principal environmental factor rather than temperature, TP, TN and pH in shrimp cultural enclosure ecosystems.